2023
DOI: 10.1111/imb.12838
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mitogenomic gene order in Orthoptera

Abstract: Mitochondrial gene order has contributed to the elucidation of evolutionary relationships in several animal groups. It generally has found its application as a phylogenetic marker for deep nodes. Yet, in Orthoptera limited research has been performed on the gene order, although the group represents one of the oldest insect orders. We performed a comprehensive study on mitochondrial genome rearrangements (MTRs) within Orthoptera in the context of mitogenomic sequence-based phylogeny. We used 280 published mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…In our study, we observed discrepancies between the ML and BI analyses, and as previously observed, the BI trees exhibited higher support ( Ma and Miao, 2022 ). However, one discrepancy involves the positioning of the Myrmecophilus and Ornebius genera, where the ML tree was consistent with findings from previous studies ( Yang et al, 2021 ; Dan et al, 2022 ; Ma and Miao, 2022 ; Gaugel et al, 2023 ). Incorporating the third codon position might lead to more robust tree topologies ( Ma and Miao, 2022 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In our study, we observed discrepancies between the ML and BI analyses, and as previously observed, the BI trees exhibited higher support ( Ma and Miao, 2022 ). However, one discrepancy involves the positioning of the Myrmecophilus and Ornebius genera, where the ML tree was consistent with findings from previous studies ( Yang et al, 2021 ; Dan et al, 2022 ; Ma and Miao, 2022 ; Gaugel et al, 2023 ). Incorporating the third codon position might lead to more robust tree topologies ( Ma and Miao, 2022 ).…”
Section: Discussionsupporting
confidence: 84%
“…This type is characterized by featuring the typical trnN-trnS1-trnE gene order and the transposition of trnV to the site between 12S and the T+A-rich region ( Ma and Li, 2018 ). The trnV relocation is also observed in Trigonidiidae, implying that it occurred independently in these two branches ( Gaugel et al, 2023 ). Moreover, Type IVG differs from Type IV described by Dan et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic position of Chorthippus marocanus aligns with the classification adopted in the Orthoptera Species File, which places it within the species group biguttulus (Linnaeus, 1758). The complex relationships within the Gomphocerini tribe have been previously observed and explained in various molecular studies (e.g., Dumas et al 2010;Nattier et al 2011;Vedenina and Mugue 2011;Hawlitschek et al 2017;Sukhikh et al 2019;Nolen et al 2020;Hawlitschek et al 2022Hawlitschek et al , 2023Gaugel et al 2023). Additionally, Hodjat and Saboori (2021) addressed the challenges and instability in the taxonomic classification of Gomphocerini species, attributing them to variations and plasticity in morphological characteristics, behaviour and acoustic communication influenced by environmental stress and hybridisation between populations.…”
Section: Phylogenetic Relationships Of Gomphocerinae Speciesmentioning
confidence: 87%